Economic-financial diagnosis and prediction of SMEs: An application to the contructin sector - Valeria Scherger; Antonio Terce\~no; Hernán P. Vigier (The International Journal of Management Science and Information Technology (IJMSIT), 2016)
The aim of this paper is to improve one of the limitations of the fuzzy models of business failure. In this sense an application to a group of small and medium -sized enterprises (SMEs) from the construction sector is introduced in a given time horizon to test the diagnosis model capacity to predict diseases. This simulation involves the adaptation of the methodological hypothesis, and the definition of the main variables that interact in the estimation. This research presents the estimation of the matrix of economic-financial knowledge and verifies its capacity of diagnosis. Also, a goodness measure, through approximate solutions, is introduced to test the model's functionality with companies outside initial sample to demonstrate its ability to predict. Therefore, through this simulation some of the fuzzy model's restrictions are overcome, the theoretical postulates are adapted; the difficulties associated with the estimation are solved and new criteria and guidelines that enrich the original theoretical model are defined. This application to SMEs can encourage the development of suitable computer systems for monitoring firms' problems, alert failures and ease decision-making. An increased of management efficiency is also expected.
Keywords: 650; economic-financial diagnosis; prediction; symptoms and causes; fuzzy relations; goodness measure